To prove cos3theta +2cos5theta +cos7theta/costheta +2cos3theta +cos5theta=cos2theta-sin2theta×tan3theta ?

1 Answer
Jul 22, 2018

Please refer to a Proof in Explanation.

Explanation:

"The Expression"=(cos3theta+2cos5theta+cos7theta)/(costheta+2cos3theta+cos5theta)The Expression=cos3θ+2cos5θ+cos7θcosθ+2cos3θ+cos5θ.

"The Nr."=(cos3theta+2cos5theta+cos7theta)The Nr.=(cos3θ+2cos5θ+cos7θ)

=(cos7theta+cos3theta)+2cos5theta=(cos7θ+cos3θ)+2cos5θ,

=2cos((7theta+3theta)/2)cos((7theta-3theta)/2)+2cos5theta=2cos(7θ+3θ2)cos(7θ3θ2)+2cos5θ,

=2cos5thetacos2theta+2cos5theta=2cos5θcos2θ+2cos5θ,

:." The Nr."=2cos5theta(cos2theta+1).

"On similar lines the Dr."=2cos3theta(cos2theta+1).

:."The Exp."=(cos5theta)/(cos3theta),

={cos(3theta+2theta)}/(cos3theta),

={cos3thetacos2theta-sin3thetasin2theta}/(cos3theta),

=(cos3thetacos2theta)/(cos3theta)-(sin3thetasin2theta}/(cos3theta),

=cos2theta-(sin2theta){(sin3theta)/(cos3theta)},

=cos2theta-sin2theta*tan3theta, as desired!